2021
DOI: 10.1002/jcp.30288
|View full text |Cite
|
Sign up to set email alerts
|

miR‐21‐regulated M2 polarization of macrophage is involved in arsenicosis‐induced hepatic fibrosis through the activation of hepatic stellate cells

Abstract: Arsenicosis induced by chronic exposure to arsenic is recognized as one of the main damaging effects on public health. Exposure to arsenic can cause hepatic fibrosis, but the molecular mechanisms by which this occurs are complex and elusive. It is not known if miRNAs are involved in arsenic‐induced liver fibrosis. We found that in the livers of mice exposed to arsenite, there were elevated levels of microRNA‐21 (miR‐21), phosphorylated mammalian target of rapamycin (p‐mTOR), and arginase 1 (Arg1); low levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 61 publications
0
29
1
Order By: Relevance
“…Taken together, miR-21 was determined as a fibrosis-associated miRNA, which could induce inflammation by activating IL-6 expression in LF tissue, resulting in LF fibrosis and hypertrophy. Like miR-221, accumulated studies have considered microRNA-21 as a central regulator of fibrotic diseases (e.g., hepatic fibrosis, skin fibrosis, and cardiac fibrosis) via various targets or molecular mechanism (e.g., inflammation, immunoreaction, and autophagy) (Yan et al, 2020;Sun et al, 2021;Xue et al, 2021). Thus, miR-21 as a potential diagnostic or therapeutic target for fibrosis diseases should be highlighted in future.…”
Section: Mir-221mentioning
confidence: 99%
“…Taken together, miR-21 was determined as a fibrosis-associated miRNA, which could induce inflammation by activating IL-6 expression in LF tissue, resulting in LF fibrosis and hypertrophy. Like miR-221, accumulated studies have considered microRNA-21 as a central regulator of fibrotic diseases (e.g., hepatic fibrosis, skin fibrosis, and cardiac fibrosis) via various targets or molecular mechanism (e.g., inflammation, immunoreaction, and autophagy) (Yan et al, 2020;Sun et al, 2021;Xue et al, 2021). Thus, miR-21 as a potential diagnostic or therapeutic target for fibrosis diseases should be highlighted in future.…”
Section: Mir-221mentioning
confidence: 99%
“…However, tumoral miR-21 is inversely associated with the densities of CD3 + and CD45RO + cells in colorectal cancers 52 . Furthermore, miR-21 promotes M2 polarization 53 , and our previous work has shown that miR-21-containing TEXs are potent regulators of TAMs through the promotion of M2-like activation 7 . Here, we further revealed that miR-21-containing TEXs inhibited NLRP3 in ammasome activity.…”
Section: Discussionmentioning
confidence: 94%
“…Kupffer cells are liver-residing macrophages that play important roles in developing of hepatic insulin resistance and fibrosis induced by diet ( 202 , 203 ). In vitro treatment of THP-1 derived macrophages with sodium arsenite (up to 8 µM for 48 h) promoted differentiation into M2 macrophages, inducing secretion of fibrogenic cytokines via upregulation of the miRNA miR-21 ( 204 ). This pathway correlated with the observation in the liver from C57BL6 mice exposed to 40 ppm of sodium arsenite for six months.…”
Section: Arsenic Effects On Inflammation and Immune Systemmentioning
confidence: 99%